I-respeto an advocacy campaign on promoting the LRT-2 accessible facilities of the blind in Metro Manila - Bomediano, Jia Mae E.; Virina, Conrado F. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
There is a group of people who society tries to ignore and fails to see- the blind. They are also citizens and have to be treated as such. Like any other person, they study, work, shop, read, write and enjoy art. Not a lot of people know it but they also watch movies, surf the net and actually own touch screen smart phones. Just because they do or access things differently does not mean they are classified as others.They deserve respect, understanding and treatment as you would give to a normal sighted person. One of the obstacles that the blind encounter daily is transport. How are they going to reach their workplaces in the safest, cheapest and most convenient way possible? They are limited to public transportation because it represents the only possibility for them to be mobile. The LRT-2 has blind user-friendly facilities for the blind to be able to travel safely and independently. These are the yellow tiles, textured handrails and other textural indicators. These play a huge role to their independence, productivity and social participation. The LRT-2 efforts to help the blind attain self-reliance will be futile if the blind do not fully utilize the blind user-friendly facilities. Reasons for not using the facilities are discouragement form their concerned family members, and, mistreatment and misunderstanding from their fellow passengers, hired guides and station guards. This advocacy campaign aims to help the blind gain access to these facilities provided for them, so that they may be able to exercise their rights and be recognized as active members in our society. It aims to teach the sighted the proper etiquette and treatment in the LRT-2 in regards to the blind introduce the blind user-friendly facilities, and encourage respect towards the blind. The campaign intends to familiarize the sighted and then make it a practice. Also, this thesis supports the idea that visual communication can benefit the blind despite them not being able to be to see.
Thesis (Bachelor of Fine Arts (Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 107-114.
Keywords: Blind--Services for; Barrier-free design for people with visual disabilities